Ages in conflict : a cross-cultural perspective on inequality between old and young - Foner, Nancy, 1945- (New York : Columbia University Press, 1984)
1. Aged--Cross--cultural studies 2. Conflict of generations--cross--Cultural studies
Includes index.
Faculty
Keywords: Older people -- Cross-cultural studies; Conflict of generations -- Cross-cultural studies